PERLINDUNGAN HUKUM GEN-Z KORBAN CYBERBULLYING DI PROBOLINGGO MELALUI RESTORATIVE JUSTICE (Berdasarkan Undang-Undang Perlindungan Anak) - Linta Alfatih, Hafifah Laila; Sidarta, Dudik Djaja; Paramitha, Vallencia Nandya; Aranggraeni, Renda (Gapenas Publisher, 2025)
The misuse of cyberbullying against Generation Z (Gen-Z) teenagers is increasing in line with the rapid development of digital technology and social media. The viral case in Probolinggo involving Luluk Nuril shows how insults, public shaming, and verbal abuse in the digital space can have serious psychological effects on victims. The urgency of this research lies in the need to assess the extent to which existing legal instruments are able to provide protection for victims of cyberbullying while offering more humane alternatives through a restorative justice approach. This study seeks to answer two main questions: what form of legal protection is available for Gen-Z teenagers who are victims of cyberbullying within the framework of Indonesian regulations, and how relevant is restorative justice as a model for resolving such cases? The method used is normative legal research with a legislative approach and case studies. Primary legal materials include the Child Protection Law, the Electronic Information and Transaction Law, the Criminal Code, and the Juvenile Criminal Justice System Law. Data was collected through literature studies and analysed using normative and comparative legal methods to test the effectiveness of applicable legal protection. The results of the study show that although legal regulations exist, the implementation of protection for victims is still weak due to normative gaps, low digital literacy, and a lack of understanding among law enforcement officials. These findings confirm the need for more specific regulatory reforms regarding cyberbullying, capacity building for officials, and the application of restorative justice to ensure the best interests of victims. The conclusion of this study is that legal protection for adolescent victims of cyberbullying must be directed towards the integration of preventive, repressive, and restorative approaches. Further research is recommended to explore the implementation of restorative justice in juvenile court practices and educational institutions as an effort to create a safer digital space.